-9-8x=-9x+16

Simple and best practice solution for -9-8x=-9x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-8x=-9x+16 equation:


Simplifying
-9 + -8x = -9x + 16

Reorder the terms:
-9 + -8x = 16 + -9x

Solving
-9 + -8x = 16 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-9 + -8x + 9x = 16 + -9x + 9x

Combine like terms: -8x + 9x = 1x
-9 + 1x = 16 + -9x + 9x

Combine like terms: -9x + 9x = 0
-9 + 1x = 16 + 0
-9 + 1x = 16

Add '9' to each side of the equation.
-9 + 9 + 1x = 16 + 9

Combine like terms: -9 + 9 = 0
0 + 1x = 16 + 9
1x = 16 + 9

Combine like terms: 16 + 9 = 25
1x = 25

Divide each side by '1'.
x = 25

Simplifying
x = 25

See similar equations:

| -3(8-4x)=4(x+2) | | ax^2+b=c | | -5x-45=-9x+67 | | A+bi=13+7i | | -3x-27=-6x+27 | | 9x-99+8x-36=86 | | u+41=v+48 | | 2x+y=11(1) | | n-2-7=-(6n-5)-5(n-2) | | 16.3+s=36.94 | | x^5-6x^2+9x-3=0 | | x^5-6x^2+9x-3=0 | | x^5-6x^2+9x-3=0 | | 15-9d-4d=5-3d | | x^5-6x^2+9x-3=0 | | 4.0p+14.10=4.50(p+3) | | 7x+9=90 | | 15-9d-4d=5-3d | | 3-17x=-31 | | 16.3+s=36.94 | | n-2-7=-(6n-5)-5(n-2) | | 4.0p+14.10=4.50(p+3) | | n-2-7=-(6n-5)-5(n-2) | | 7x+9=90 | | 3x-9+(x+7)=90 | | X=12-y | | n-2-7=-6(6n-5)-5(n-2) | | 150=x(60) | | 5x-22+(4x+4)=90 | | .75a=14.25 | | 50x^2=450 | | 3.2x-0.88+1.2x=0 |

Equations solver categories